Two monosodium salt hydrates of Colour Index Pigment Red 48. Issue 8 (6th July 2020) - Tapmeyer, Lukas; Hill, Steven; Bolte, Michael; Hützler, Wilhelm Maximilian
Abstract : Two hydrate crystal structures of Colour Index Pigment Red 48 are characterized and the hydration and dehydration behaviour of the pigment are evaluated. Abstract : We report herein the crystal structures of a monohydrate of Colour Index Pigment Red 48 (P.R.48) (systematic name: monosodium 2‐{2‐[3‐carboxy‐2‐oxo‐1, 2‐dihydronaphthalen‐1‐ylidene]hydrazin‐1‐yl}‐4‐chloro‐5‐methylbenzenesulfonate monohydrate), Na + ·C18 H12 ClO6 S − ·H2 O, and a dihydrate, Na + ·C18 H12 ClO6 S − ·2H2 O. The two monosodium salt hydrates of P.R.48 were obtained from in‐house synthesized P.R.48. Both have monoclinic ( P 21 / c ) symmetry at 173 K. The crystal packing of both crystal structures shows a layer arrangement whereby N—H…O and O—H…O hydrogen bonds are formed.